2012
DOI: 10.1063/1.4766414
|View full text |Cite
|
Sign up to set email alerts
|

Using an Au interlayer to enhance electron field emission properties of ultrananocrystalline diamond films

Abstract: We observe that an Au interlayer markedly enhances the electrical field emission (EFE) properties of ultrananocrystalline diamond (UNCD) films on Si substrates. The EFE properties of UNCD/Au/Si films can be turned on at a lower field and attain a higher current density than in UNCD films grown on Si substrates without an Au interlayer. Transmission electron microscopy reveals that the Au interlayer induces the formation of SiC clusters, preventing the formation of a resistive amorphous carbon layer that nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…[1][2][3] The sp 2 -bonded carbon in the grain boundaries of NCD films is the genuine factor for the enhanced FEE properties of these films as compared with MCD films. 4,5 The non-diamond carbon is not conductive enough, restricting the FEE characteristics achievable for NCD films. Facilitating the formation of nanographitic phases in the grain boundaries due to nitrogen addition (>20%) in the CH 4 /Ar plasma can improve the electrical conductivity (EC) that enhances the FEE properties of diamond films.…”
mentioning
confidence: 99%
“…[1][2][3] The sp 2 -bonded carbon in the grain boundaries of NCD films is the genuine factor for the enhanced FEE properties of these films as compared with MCD films. 4,5 The non-diamond carbon is not conductive enough, restricting the FEE characteristics achievable for NCD films. Facilitating the formation of nanographitic phases in the grain boundaries due to nitrogen addition (>20%) in the CH 4 /Ar plasma can improve the electrical conductivity (EC) that enhances the FEE properties of diamond films.…”
mentioning
confidence: 99%
“…39,40 There have been great efforts in improving the EFE of UNCD films via the suppression of the appearance of an a-C phase present at the diamond−Si interface. 41,42 It has been reported that the turn-on field of diamond films can be lowered markedly due to the elimination of the a-C phase via the utilization of Au coating as interlayer. 41,42 However, it is a complicated process, as the thickness of the Au coating needs to be critically controlled.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The process of Au and Cr deposition on Si and the pre-seeding process for the growth of diamond on these Au(Si) substrates are described in detail elsewhere. 15,16 The UNCD films were first deposited using microwave plasma enhanced chemical vapor deposition (MPECVD) system in Ar(99%)/CH 4 (1%) plasma under 1200 W and 120 Torr for 90 min. The plane view scanning electron microscopy (SEM; Jeol 6500) image shown in Fig.…”
mentioning
confidence: 99%
“…Hence, the formation of Au(Si) eutectic layer eliminates the origin of the a-C phase in the vicinity of interface, which lowers the resistivity of the interface layer. 15,16 Seemingly, the SiC was formed due to the interaction of Si and C species, i.e., the Si species have diffused through the Au(Si) eutectic layer to react with the carbon promptly, forming SiC. The SiC can enhance the efficiency for the nucleation of diamond.…”
mentioning
confidence: 99%
See 1 more Smart Citation